Modelagem e simulação de uma unidade industrial de produção de ácido sulfúrico integrada a uma planta de geração de energia elétrica - Chagas, Marcelo Martins das (2021)
In the next few decades, population growth will demand increased production of fertilizers and, consequently, raw materials as sulfuric acid. In this scenario, the recent studies have focused on the development of computational models for process optimization. In the past few decades, process modelling had limited progress in industry. Efforts have been made in model developments focused on petrochemical industry and, hence, there is a lack of mathematical models of satisfactory reliability for a wide range of industrial processes. In this work, a process simulation was developed and validated using project data from an actual industrial sulfuric acid plant located in Araxá, Minas Gerais. Commercial process simulators had been used. Unit operations, components and integrated systems of the industrial plant were modelled. A mathematical formulation was built to described equilibrium constant behavior for SO2 oxidation. Isentropic efficiency of two steam turbines were calculated for the model development. To validate the simulations, thermodynamic models were used to express chemical components. Simulation results good agreement with plant data using COCO and UniSim with relative error maximum of 3.1%. For the steam generation system integrated to process gas system, some limitations in the superheater model have been detected, but some refinements must be done. For the sulfur furnace, simulations using UniSim had errors of 9,5% higher than a traditional simulation implemented in Maple (0,3%).